Penyusunan Anggaran dan Pengawasan Internal, Pengaruhnya Terhadap Kinerja Akedemik di IAIN Sultan Amai Gorontalo - Sulam Sulam (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
Academic Performance and Internal Oversight is something that needs to be examined, in the analysis whether there is a correlation with Academic Performance. The purpose of this study was to determine: (1) Correlation between Budgeting and Academic Performance, (2). Correlation of Internal Oversight with Academic Performance and (3) Joint correlation between Budgeting and Internal Oversight with Academic Performance at IAIN Sultan Amai Gorontalo. This thesis writing method uses a quantitative method in which all data are analyzed using the SPSS Application program in partial analysis using simple regressions and for two variables together between Budgeting and Internal Oversight with Academic performance analyzed by using multiple regression analysis (multiple regression). The results of the study show that the dependent variable of Budgeting (X1) partially has a very strong influence on the improvement of Academic Performance. It is shown that from the value of r table with data significance at the 0.05 level of 1.669 after calculated, the death correlation using tcount = 4.158 while ttable = 1.669 with a significance value of 4.158> 1.669, the results of the hypothesis regressions are accepted. As for testing the dependent variable (X2) / Internal Oversight with academic performance of the rtable determined at 0.05 on the rtable value of 1.669 after calculated with the regressions formula produces a t count of 1.00, the value of rtable is smaller than the value of tcount: Ha 1.00 ≤ Hi 1.669, this means that partially there is no relationship between internal supervision with academic performance. While Hypothesis Test dependent variable jointly between Budgeting and Internal Oversight with Academic Performance there is a strong influence is shown by the results of the calculation of rtable 0.05 of 1.669 greater with tcount of 0.19 in accordance with the calculation of multiple regression. The conclusion in this thesis is that partially (person test) Budgeting has a positive effect on improving Academic Performance, and Internal Oversight partially has no effect on improving academic performance, but jointly between budgeting and Internal Supervision is very influential on improving academic performance at IAIN Sultan Amai Gorontalo.